(The first companions who migrated to Abyssinia) (Journal of the College of Basic Education, 2022)
Research SummaryI have chosen to search the tagged (the first companions who migrated to Abyssinia) to indicate the heroic position of those heroes who confronted the idolaters of Quraish in defense of the Islamic religion and to raise the banner of Islam high, and after the number increased God (peace be upon him) to emigrate to the land of Abyssinia.